Extreme risk transmission among bitcoin and crude oil markets. (August 2022) - Li, Dongxin; Hong, Yanran; Wang, Lu; Xu, Pengfei; Pan, Zhigang
Abstract: In the period of extreme events, this paper aims to study the extreme risk transmission between Bitcoin and crude oil market by using the extreme Granger causality test to test their causal relationship under extreme and non-extreme shocks. First, we can obtain different shocks of Bitcoin and crude oil returns based on empirical quantiles. Second, considering the different role that these shocks played in the causality between Bitcoin and crude oil, we conduct our research by testing the causality among different pairwise shocks. Further, given that these relationships may be changed at different time horizons, we also detect them from a frequency-domain perspective. Hence, we not only find the strong evidence of extreme risk transmission between Bitcoin and crude oil but also investigate the time-varying characteristic of this transmission, which may have a great impact on market participants and scholars related to Bitcoin-oil relations. Editor highlights: We detect the time- and frequency-domain extreme oil-Bitcoin causality. We confirm the presence of extreme asymmetry in the oil-Bitcoin linkage. The asymmetric relationship is sensitive to the degree of both price movements. We verify the existence of their time-varying causality at different timescales.